High Frequency Link Power Conversion System for Fuel cell Applications - Babu, A. R. Vijay; Venkatesh, P.M.; Suresh, Dr.K. (International Journal of Engineering and Technology, 2018)
In this paper an empirical model of the air breathing (ABFC) is proposed to investigate the cell voltage verses current density characteristics and harnessing of maximum energy from natural resource whenever it’s available. The power electronic converters role is important in between source and load. Proper controller can switch the converter in the desired time and improve the system performance and stability. The mathematical model of the ABFC is built in MATLAB/Simulink. The proposed system also has boost converter, bidirectional DC-DC converter and inverter for grid and energy integration. The boost inverter/buck rectifier in this system is controlled by ANFIS controller is for better output, boost and bidirectional DC-DC converters are controlled by PID controller in closed loop. Overall operations are based on modes main controller, which control the system operation in different modes. Any variations happening in the input, storage and load parameters, the controller changes the mode and operates the system in effective way.